Pathogenicity of E. coli O78 Riemerella anatipestifer Chicken Isolate either alone or in combination in Ducks - Khedr, Afaf Ahmed; Soliman, Eman M.; Gamal, Fatma El Zahraa; Mohamed, Fatma; Mohmed, , Gina M.; Sayed, Marwa Fathy El (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The objective of this study was to find the relation between the pathogenicity of (E. coli) O78 chicken isolate alone or mixed with Riemerella anatipestifer infection by conventional methods and modern techniques. The results of this study revealed that the pathogenicity of all groups of Riemerella anatipestifer (RA) was 100% while it was 90% among the ducks inoculated with E. coli and was 100% in the injected with both strains of Riemerella anatipestifer and E. coli together and 0% in the control negative group. RA and E. coli strains were correctly identified using the VITEK 2 compact system with 99% and 94% probability, respectively. The results of polymerase chain reaction confirmed the identification results using specific primers either for E. coli O78 or Riemerella anatipestifer giving products 720bp and 665bp, respectively. Histopathological examination revealed that liver showed congestion in blood vessels and hepatic cell necrosis in the group inoculated within Riemerella anatipestifer, While liver showed only congested blood vessels in E. coli inoculated group. On the other hand, Liver showed severe vacuolar degeneration with focal amyloid infiltration in E. coli and Riemerella inoculated group
Keywords: Duck; E. coli; Pathogenicity; Riemerella anatipestifer